Methods of Assessment of Physical Capacity in People with Diabetes Mellitus Type 1 - Flotyńska, Justyna; Szybiak, Weronika; Naskret, Dariusz; Zozulinska-Ziolkiewicz, Dorota; Grzelka-Wozniak, Agata; Uruska, Aleksandra (Current Diabetes Reviews, 2024)
Background: The article aims to present the most popular methods of assessing physical capacity. Moreover, the article sheds light on the beneficial impact of improving physical capacity in people with Diabetes Mellitus type 1 (DM1). Methods: A computer-based literature search of PubMed, SCOPUS and Web of Science included studies up to September 2022. Results: The significant role of regular physical exertion could be observed in the group of people suffering from DM1, which implicates a positive correlation between the activity and the remission time. A suitable and objective indicator of sport influence on the organism is physical capacity (PC), which describes the efficiency of the cardiovascular system and its correlation between BMI, sex, and age. PC is mostly shown as VO2max. Well metabolically controlled DM1 is not a contraindication to stress test. Even though physical activity is closely related to human history, the range of research into the importance of PC is still limited to particular groups of patients, which presents an opportunity for further research and future conclusions. Conclusions: Undertaking physical activities has a multidirectional influence on the organism. According to up-to-date knowledge, various methods of PC assessment are available. Patients can choose more easily accessible, simpler, and cheaper options like CRT, RT, and HST which do not need specialized equipment and skills. They can also decide on more advanced examinations like ergospirometry, where direct measurements of VO2max and other cardiorespiratory parameters are made.
Keywords: VO2max